ANALISIS CAPITAL ASSET PRICING MODEL PADA SEKTOR ENERGI PERIODE 2020-2022 - Yanti, Pitri; Ramadhani, Indi; Sari, Maya (Jurnal Ekonomi Manajemen, 2023)
This study used the capital asset pricing model (CAPM) to examine the return and risk levels of energy sector stock performance to identify efficient and inefficient groups of stocks. For the purpose of this study, a sample of 28 stocks from the energy sector listed on the Indonesia Stock Exchange for the 2020–2022 timeframe was chosen using a purposive sampling technique. Six out of the 28 equities, according to the analysis's findings, are considered to be high risk. PT Medco Energi Internasional and PT Perdana Karya Perkasa Tbk are the two stocks with the greatest and lowest respective levels of risk. Nine shares of firms out of the 28 stocks tested fall under the category of inefficient stocks (overvalued), whereas 19 other stocks fall under the category of efficient stocks (undervalued). Selling overvalued stocks and purchasing undervalued ones are two different financial decisions that should be made. Overvalued stocks should be sold, while undervalued stocks should be purchased.